Diet as an Exposure Source and Mediator of Per- and Polyfluoroalkyl Substance (PFAS) Toxicity - Roth, Katherine; Imran, Zunaira; Liu, Wanqing; Petriello, Michael C. (Frontiers in Toxicology, 2020)
Per- and polyfluoroalkyl substances (PFAS) are ubiquitously found in the environment due to their widespread commercial use and high chemical stability. Humans are exposed primarily through ingestion of contaminated water and food and epidemiological studies over the last several decades have shown that PFAS levels are associated with adverse chronic health effects, including cardiometabolic disorders such as hyperlipidemia and non-alcoholic fatty liver disease. Perhaps the most well-established effects, as demonstrated in animal studies and human epidemiological studies, are the metabolic alterations PFAS exposure can lead to, especially on lipid homeostasis and signaling. This altered lipid metabolism has often been linked to conditions such as dyslipidemia, leading to fatty liver disease and steatosis. Western diets enriched in high fat and high cholesterol containing foods may be an important human exposure route of PFAS and may also act as an important modulator of associated toxicities. In fact, the chemical structure of PFAS resemble fatty acids and may activate some of the same signaling cascades critical for endogenous metabolism. In this review we aim to outline known dietary exposure sources of PFAS, describe the detrimental metabolic health effects associated with PFAS exposure, and focus on studies examining emerging interaction of dietary effects with PFAS exposure that further alter the dysregulated metabolic state.